Carbolic Acid before Joseph Lister: Rail Ties, Sewage, Manure, and the Great Stink. Issue 3 (March 2020) - Ehrhardt, John D.; Nakayama, Don K.; O'Leary, J. Patrick
Before Joseph Lister's landmark Lancet publications on the use of carbolic acid wound dressings in 1867, surgeons Jules Lemaire in France and Enrico Bottini in Italy had already used carbolic acid on hundreds of patients to control suppurative wounds. After Friedlieb Runge isolated it from coal tar in 1834, a number of scientists recognized the efficacy of carbolic acid in preventing decay and neutralizing the stench of dead animals and human cadavers. Frederick Calvert, Alexander McDougall, and Angus Smith in Manchester promoted a powdered form of carbolic acid as a deodorizing agent to treat municipal sewage across the United Kingdom, most notably during London's famous "Great Stink" of 1858. Edmond Corne in France introduced his formulation, which Alfred-Armand-Louis-Marie Velpeau, Ferdinand LeBeuf, and Lemaire adapted for clinical use in 1859. Lemaire wrote extensively on carbolic acid and its surgical application in three publications from 1860 to 1862. In 1866, Bottini published his experience of 600 cases where it was used. In 1865, Lister began to use carbolic acid in open fractures after Thomas Anderson, his colleague in agricultural chemistry at the University of Glasgow, told him about its use in Carlisle sewage works. This article traces the rich history of carbolic acid from an unknown compound in coal to the cornerstone of Listerism in late-19th–century operating rooms.